LIBRARIANS' STRATEGIES IN INCREASING PUBLIC INTEREST IN VISITING THE NORTH SUMATRA PROVINCIAL LIBRARY AND ARCHIVES OFFICE - Silva Lestari Hasibuan; Retno Sayekti (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to identify and describe librarians' strategies for increasing public interest in visiting the North Sumatra Provincial Library and Archives Service (Dispusip Provsu) and to analyze the various factors hindering its implementation. This study employed a qualitative approach with descriptive methods. Data were collected through in-depth interviews, participant observation, and documentation studies. Data analysis techniques followed the Miles and Huberman interactive model, which encompasses data reduction, data presentation, and conclusion drawing. The research results show that the strategy to increase visitor interest at the North Sumatra Provincial Library and Archives Service focuses on optimizing digital promotion, outreach services, and adaptive community-based literacy activities. Librarians play a crucial role as agents of change through excellent service and information technology integration to build an inclusive literacy ecosystem. However, the effectiveness of this strategy is still hampered by infrastructure constraints, low public digital literacy, and limited budget and human resource competencies. Successfully transforming libraries into modern learning centers requires a systemic commitment from local governments to mitigate these obstacles to ensure the program's sustainability amidst information disruption. This study aims to identify and describe librarians' strategies for increasing public interest in visiting the North Sumatra Provincial Library and Archives Service (Dispusip Provsu) and to analyze the various factors hindering its implementation. This study employed a qualitative approach with descriptive methods. Data were collected through in-depth interviews, participant observation, and documentation studies. Data analysis techniques followed the Miles and Huberman interactive model, which encompasses data reduction, data presentation, and conclusion drawing. The research results show that the strategy to increase visitor interest at the North Sumatra Provincial Library and Archives Service focuses on optimizing digital promotion, outreach services, and adaptive community-based literacy activities. Librarians play a crucial role as agents of change through excellent service and information technology integration to build an inclusive literacy ecosystem. However, the effectiveness of this strategy is still hampered by infrastructure constraints, low public digital literacy, and limited budget and human resource competencies. Successfully transforming libraries into modern learning centers requires a systemic commitment from local governments to mitigate these obstacles to ensure the program's sustainability amidst information disruption. This study aims to identify and describe librarians' strategies for increasing public interest in visiting the North Sumatra Provincial Library and Archives Service (Dispusip Provsu) and to analyze the various factors hindering its implementation. This study employed a qualitative approach with descriptive methods. Data were collected through in-depth interviews, participant observation, and documentation studies. Data analysis techniques followed the Miles and Huberman interactive model, which encompasses data reduction, data presentation, and conclusion drawing. The research results show that the strategy to increase visitor interest at the North Sumatra Provincial Library and Archives Service focuses on optimizing digital promotion, outreach services, and adaptive community-based literacy activities. Librarians play a crucial role as agents of change through excellent service and information technology integration to build an inclusive literacy ecosystem. However, the effectiveness of this strategy is still hampered by infrastructure constraints, low public digital literacy, and limited budget and human resource competencies. Successfully transforming libraries into modern learning centers requires a systemic commitment from local governments to mitigate these obstacles to ensure the program's sustainability amidst information disruption. This study aims to identify and describe librarians' strategies for increasing public interest in visiting the North Sumatra Provincial Library and Archives Service (Dispusip Provsu) and to analyze the various factors hindering its implementation. This study employed a qualitative approach with descriptive methods. Data were collected through in-depth interviews, participant observation, and documentation studies. Data analysis techniques followed the Miles and Huberman interactive model, which encompasses data reduction, data presentation, and conclusion drawing. The research results show that the strategy to increase visitor interest at the North Sumatra Provincial Library and Archives Service focuses on optimizing digital promotion, outreach services, and adaptive community-based literacy activities. Librarians play a crucial role as agents of change through excellent service and information technology integration to build an inclusive literacy ecosystem. However, the effectiveness of this strategy is still hampered by infrastructure constraints, low public digital literacy, and limited budget and human resource competencies. Successfully transforming libraries into modern learning centers requires a systemic commitment from local governments to mitigate these obstacles to ensure the program's sustainability amidst information disruption.